2019
DOI: 10.4103/jmas.jmas_67_18
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus conventional open surgery in T4 rectal cancer: A case–control study

Abstract: Background:Laparoscopic surgery (LAS) for T4 rectal cancer (RC) is still controversial. This study aims to compare LAS with conventional open surgery in patients with T4 RC.Patients and Methods:Patients undergoing laparoscopic or open curative resection for T4 RC from January 2010 to September 2014 in our hospital were enrolled. Patients’ clinicopathological characteristics and survival outcomes were collected and compared. All statistical analysis was performed using SPSS 22.0.Results:A total of 125 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Out of 590 articles, 22 17–36 fulfilled the selection criteria and were included in the systematic review, with a total of 1055 patients with MVR. Figure 1 is a flow chart demonstrating the study search, selection and inclusion criteria applied in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 590 articles, 22 17–36 fulfilled the selection criteria and were included in the systematic review, with a total of 1055 patients with MVR. Figure 1 is a flow chart demonstrating the study search, selection and inclusion criteria applied in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Out of 590 articles, 22 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] fulfilled the selection criteria and were included in the systematic review, with a total of 1055 patients with MVR. Figure 1…”
Section: Literature Searchmentioning
confidence: 99%
“…All the guidelines suggest T4 rectal cancer as a contraindication for laparoscopic surgery, because the locally advanced tumor have a high risk of CMR or need en bloc resection of the adjacent infiltrated organs which might increase the convention rates and collateral increasing morbidity. Some studies have assessed the pathologic and oncologic results and suggested that laparoscopic surgery was feasible for T4 colorectal cancer 108,124 . In this study, laparoscopic resection for all the stages of rectal cancer were merged and generally compared with open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have assessed the pathologic and oncologic results and suggested that laparoscopic surgery was feasible for T4 colorectal cancer. 108,124 In this study, laparoscopic resection for all the stages of rectal cancer were merged and generally compared with open surgery. In that case, the analysis to some foci of controversy was ignored, such as T4 tumor, resection of primary tumor following nCRT and so on.…”
Section: Survival Outcomesmentioning
confidence: 99%
“…Одно из наиболее крупных исследований было выполнено китайскими специалистами [32]. Оно являлось ретроспективным и включило 125 больных раком прямой кишки pT4, получивших лечение в Западно-китайский госпитале при Сычуаньском университете.…”
Section: Introductionunclassified